2020
DOI: 10.1007/s10742-020-00213-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive coercion sometimes works: evaluating whether young African-American women who experience reproductive coercion or birth control sabotage are more likely to become pregnant

Abstract: Men engaging in reproductive coercion may coerce, force, or deceive female partners into pregnancy. This study evaluates whether the 3-month incidence of pregnancy is higher among women reporting reproductive coercion than similar women reporting no reproductive coercion. We tested this hypothesis in longitudinal data from a sample of African-American women ages 18–24 recruited from community settings in Atlanta, Georgia, US, in 2012–2014 (n = 560). Participants were surveyed at baseline, 3 months, 6 months, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…One potential predictor of men’s coercive CUR strategies is their history of unintended partner pregnancy—which is a common outcome for condomless sex in the United States (Trussell, 2007), a potential salient consequence of coercive CUR strategies (Czechowski et al, 2019; Davis, 2019; Rosenbaum & DiClemente, 2020; Tarzia et al, 2020), and of sexual violence more broadly (Basile et al, 2022; Gomez, 2011; Miller & Silverman, 2010). Men’s history of unintended partner pregnancy may influence their use of coercive CUR strategies.…”
Section: Past Unintended Partner Pregnancy Alcohol Intoxication and M...mentioning
confidence: 99%
“…One potential predictor of men’s coercive CUR strategies is their history of unintended partner pregnancy—which is a common outcome for condomless sex in the United States (Trussell, 2007), a potential salient consequence of coercive CUR strategies (Czechowski et al, 2019; Davis, 2019; Rosenbaum & DiClemente, 2020; Tarzia et al, 2020), and of sexual violence more broadly (Basile et al, 2022; Gomez, 2011; Miller & Silverman, 2010). Men’s history of unintended partner pregnancy may influence their use of coercive CUR strategies.…”
Section: Past Unintended Partner Pregnancy Alcohol Intoxication and M...mentioning
confidence: 99%
“…Survivors bear a risk of psychological trauma and fearfulness of health outcomes, such as pregnancy and sexually transmitted infections (STIs; Park et al, 2016; Rosenfeld et al, 2018). Furthermore, reproductive coercion is associated with an increased risk of STIs (Rosenbaum & DiClemente, 2020; Willie et al, 2021). Willie et al (2021) found that contraceptive sabotage, a form of reproductive coercion, was associated with greater odds of having a STI, and Kazmerski et al (2015) noted that reproductive coercion was associated with repeated STI testing.…”
Section: Reproductive Coercionmentioning
confidence: 99%
“…In particular, unwanted pregnancy is a potential outcome of reproductive coercion (Miller et al, 2010, 2014; Sutherland et al, 2015). For instance, Rosenbaum and DiClemente's (2020) recent analysis of young, African American women who were identified as being at disproportionate risk of HIV found that pregnancy was a common outcome of reproductive coercion, occurring among 11.3% of women sampled. This finding is particularly salient given recent shifts in policy concerning abortion access in the United States following the United States Supreme Court overturn of Roe v. Wade , and the notion that unintended pregnancies as a result of reproductive coercion can have potentially lifelong implications (Spector-Brigady & Mello, 2022).…”
Section: Reproductive Coercionmentioning
confidence: 99%
“…La CR génère également des e ets importants sur la santé sexuelle, reproductive et mentale des femmes qui en font l'expérience. En e et, la CR est associée à de la violence verbale [11]; à des grossesses non désirées ou non plani ées [ 4,9,17]; à des infections transmises sexuellement et par le sang [15,17]; à une hausse de symptômes dépressifs ou post-traumatiques [10,16,18]; et à une probabilité accrue de polyvictimisation. [19] En résumé, le CR se situe donc à l'intersection de deux préoccupations de santé publique : la violence faite aux femmes ainsi que l'autonomie et la santé reproductive.…”
Section: Résuméunclassified